1998
DOI: 10.1103/physrevlett.81.1841
|View full text |Cite
|
Sign up to set email alerts
|

Jamming, Force Chains, and Fragile Matter

Abstract: We consider materials whose mechanical integrity is the result of a jamming process. We argue that such media are generically "fragile": unable to support certain types of incremental loading without plastic rearrangement. Fragility is linked to the marginal stability of force chain networks within the material. Such ideas may be relevant to jammed colloids and poured sand. The crossover from fragile (when particles are rigid) to elastoplastic behavior is explored.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
837
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 970 publications
(888 citation statements)
references
References 27 publications
26
837
2
2
Order By: Relevance
“…The jamming phase diagram provides a unified picture for the ergodic-nonergodic transition in systems as diverse as molecular glasses, foams, granular matter and colloidal suspensions [22]. If a system arrests as soon as it is able to support an external load, such that it responds elastically to some compatible loads while undergoing plastic rearrangments under incompatible loads, it is classified as 'fragile' [36,37,38]. Jamming of fragile matter leads to slow dynamics because of the kinetic constraints it imposes on the motion of the individual constituents.…”
Section: The Jamming Phase Diagram and The Compressed Exponential Dynmentioning
confidence: 99%
“…The jamming phase diagram provides a unified picture for the ergodic-nonergodic transition in systems as diverse as molecular glasses, foams, granular matter and colloidal suspensions [22]. If a system arrests as soon as it is able to support an external load, such that it responds elastically to some compatible loads while undergoing plastic rearrangments under incompatible loads, it is classified as 'fragile' [36,37,38]. Jamming of fragile matter leads to slow dynamics because of the kinetic constraints it imposes on the motion of the individual constituents.…”
Section: The Jamming Phase Diagram and The Compressed Exponential Dynmentioning
confidence: 99%
“…However, there are similarities in particle shape, with the exception of PS. The physical characteristics are important, as it has been reported that particles within a sample are close to a fragility limit prior to loading [22]. This means that the application of any loading, including ultrasonic vibrations, can instantaneously and significantly change the properties of the sample, and influence the force chains.…”
Section: Geological Materials Characterisationmentioning
confidence: 99%
“…This means that the application of any loading, including ultrasonic vibrations, can instantaneously and significantly change the properties of the sample, and influence the force chains. In the first stage of the compaction process, a reorientation of the particles takes place, and so particle shape is not specified to be as critical [22].…”
Section: Geological Materials Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is general knowledge now, that ensuing force chains follow certain preferential channels through the bulk collection of material (percolation sites). The distribution of these load bearing chains results in dormant regions that do not contribute to the overall force transmission and have been aptly termed as "spectators" [22]. The locations of these chains are not predictable in nature, and can be altered by agitation.…”
Section: Introductionmentioning
confidence: 99%